Adsorption of Gold from Copper–Tartrate–ThiosulfateSolutions with Ion-Exchange Resins - Yan Fu; Junnan Chen; Feng Xie; Zhichao Cao; Wei Wang (Metals, 2023)
The adsorption behavior of gold from copper–tartrate–thiosulfate solutions with ion-exchange resins was studied in this paper. Experimental parameters include resin dosage, pH, temperature, copper, tartrate, and thiosulfate concentration. A moderate increase in resin dosage, pH, temperature, and tartrate concentration is beneficial for gold adsorption, but an excessive tartrate concentration or higher temperature depresses the adsorption process. Increasing copper and thiosulfate concentrations may competitively occupy the active sites on the resin surface, leading to a reduction in the gold adsorption capacity. The XPS and FT-IR analyses indicate that copper and gold on the resin after adsorption mainly exist in the form of Cu+ and Au+, and sulfur mainly exists in the form of SO42− and S2O32−. This implies that the use of resin for gold recovery from thiosulfate leachate may face critical challenges because there is inevitably a higher content of copper and thiosulfate.